PENGARUH PENGEMBANGAN KARIR DAN PENEMPATAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT, BANK PEMBIAYAAN RAKYAT SYARIAH RAHMAH HIJRAH AGUNG DI KOTA LHOKSEUMAWE - Ikhsan, Muhammad; Nursanjaya, Nursanjaya (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
This research aims to determine the influence of career development  and work placement on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe City. This research was conducted on PT. Rahmah Hijrah Agung Lhokseumawe City. This study used primary data in the form of questionnaires  distributed to PT employees. Rahmah Hijrah Agung Lhokseumawe  City as many as 36 respondents. The data analysis methods used are instrument tests and classical assumption tests as well as multiple linear regression tests using the help of SPSS version 26 software. The results of the partial testing showed that career development did not have a significant effect on employee work performance, while work placement had a positive and significant  effect on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe  City. Meanwhile, from the results of simultaneous  testing it was obtained  that career development  and work placement  together had a significant  effect on the work performance of PT employees. Rahmah Hijrah Agung Lhokseumawe City.